Le thème du féminicide dans la littérature française au XIXe siècle - Kyoko Murata (Criminocorpus)
The aim of this article is to examine the theme of feminicide in nineteenth-century French literature. In La Fille aux yeux d'or and La Duchesse de Langeais, where Balzac projects his dream of the Orient, the hero disposes of his lover's life as her absolute master. Women are supposed to admire the strength of men and accept their violence. In contrast, George Sand's Indiana denounces male violence as a crime. While in Romantic literature the theme of feminicide is tinged with exoticism, in Naturalist literature this theme becomes closer to reality. In La Bête humaine, Zola portrays several criminal characters. Although he exploits various facts and scientific references such as Lombroso's ideas, Zola differentiates himself from them by his own social and aesthetic notions. Thus, this article highlights the fact that the theme of feminicide is permeated by men's desire and fear for women, as well as their appetite for domination.